Image of Camino de Santiago: Analysis of its promotional representation as a tourist product - Andrade Suárez, María José; Caamaño Franco, Iria (Tourism & Management Studies, 2024)
In the context of intense competition between destinations, the tourist image is an important element of differentiation. The perceived image is associated with beliefs and impressions about the destination; the projected image becomes an important phenomenon for the promotion and marketing of destinations. In this paper we analyze the promotion campaigns carried out by the regional administration about the Camino de Santiago in recent decades (the context, evolution, actors, promotion strategies, communication activities, materials and symbols) and the correspondence between communication (projected image) and the perceived image by the pilgrims (through the analysis of 2,000 surveys). The empirical study, which takes into account the tourist image of the Camino de Santiago from the point of view of tourists/pilgrims and the projected image, has confirmed the existence of some differences between both, which allows to identify the correspondence or fit between these elements to improve of destination competitiveness.